Upaya Meningkatkan Prestasi Belajar IPA melalui Pembelajaran Group Investigation di MTs Negeri 1 Bantul - Sumiasyih (Jurnal Pendidikan Madrasah, 2020)
This research aims to improve students' learning achievement in science learning through investigative group activities. This is motivated by the low learning outcomes of the "Calor and his transfer" material. Based on the daily return of 34 students, there are 24 students who have not been completed. The low learning achievement is caused by two factors, first, the student factors include low student input and low interest to the science lesson. Secondly, the teacher factor is still using conventional methods of learning. This research uses class action methods. Data analysis of quantitative and qualitative approaches. The results showed that there was an increase in science achievement ranging from the pre-cycle, from 10 students increased to 21 students on cycle 2. Group Investigation's learning methods were able to improve the VII-G student's study achievement by 61.7% significantly.